PENGARUH THIN CAPITALIZATION, KETIDAKPASTIAN LINGKUNGAN, DAN KESULITAN KEUANGAN TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2022) - Putri, Jeficca Fania; Rohman, Abdul (Diponegoro Journal of Accounting, 2024)
This research aims to test and obtain empirical evidence of the effect of thin capitalization, environmental uncertainty, and financial distress on tax avoidance. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022 with a total of 192 companies. The sample was selected using purposive sampling method.In this research, the independent variables used are thin capitalization, environmental uncertainty, and financial distress. Thin capitalization is measured using the Debt to Equity Ratio (DER), while environmental uncertainty is measured through sales volatility, and financial distress is measured using the Springate model (S-Score). While the dependent variable in this research is tax avoidance as measured by Effective Tax Rate (ETR).This research uses multiple linear regression analysis method to see how the independent variable affects the dependent variable. The results of this research indicate that thin capitalization and environmental uncertainty have a negative and significant effect on tax avoidance. While the financial distress variable has a positive and significant effect on tax avoidance.